A Review of side effects of Kombucha - Ștefania Țacu; Claudia Jude; Emil Moiș; Diana Deleanu (Archives of Clinical Gastroenterology - Peertechz Publications, 2023)
Kombucha is a mushroom fermented in sweetened black or green tea, originally found in Asia, being used as a remedy for many ailments in this region. Kombucha is not a usual mushroom because it represents the symbiosis between yeast and a variety of bacteria aggregated through a permeable membrane. Among the benefits of Kombucha tea are the potential antioxidant effect against free radicals, and the clinical effects on diabetes for its hypoglycemic, lipid-lowering, and immune stimulation. But secondary to the lack of evidence to support these benefits, several publications emerged to mention the side effects of Kombucha consumption. The present article is trying to collect the data reported in the literature regarding the side effects of Kombucha.